2017
DOI: 10.1177/1687814017710618
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Al2O3 nanofluids in minimum quantity lubrication in hard milling of 60Si2Mn steel using cemented carbide tools

Abstract: In this article, an attempt has been made to explore the potential performance of Al 2 O 3 nanoparticle-based cutting fluid in hard milling of hardened 60Si 2 Mn steel (50-52 HRC) under different minimum quantity lubrication conditions. The comparison of hard milling under minimum quantity lubrication conditions is done between pure cutting fluids and nanofluids (in terms of surface roughness, cutting force, tool wear, and tool life). Hard milling under minimum quantity lubrication conditions with nanofluid Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 26 publications
(24 reference statements)
1
44
0
Order By: Relevance
“…It can be explained that the ignition temperature of soybean oil is lower than that of water-based emulsion. Therefore, the high heat generated from hard turning makes the lubricating character of soybean oil less effective, and this observation is suitable with previous studies [12,19,34].…”
Section: The Effects Of Control Factors On the Cutting Forces And Sursupporting
confidence: 62%
See 1 more Smart Citation
“…It can be explained that the ignition temperature of soybean oil is lower than that of water-based emulsion. Therefore, the high heat generated from hard turning makes the lubricating character of soybean oil less effective, and this observation is suitable with previous studies [12,19,34].…”
Section: The Effects Of Control Factors On the Cutting Forces And Sursupporting
confidence: 62%
“…Duc, T.M. et al [19] studied the performance of Al 2 O 3 nanofluids in MQL hard milling using carbide tools. The experimental results revealed the decrease of friction coefficient, cutting forces and tool wear due to the effectiveness of Al 2 O 3 nanofluids, which led to the improvement of cutting performance, surface quality, and tool life.…”
Section: Introductionmentioning
confidence: 99%
“…Vázquez et al, mentioned that by adding the nanoparticles into the conventional cutting fluid, their thermal properties enhanced and increase the tool life [44]. Minh et al, stated that the main reason for the tool life prolonged is due to the oil mist and the number of nanoparticles formed on flank face [45]. The formed oil mist and nanoparticles in the cutting zone increases to create "roller effect" which eventually reduce the cutting force and tool wear.…”
Section: Tool Lifementioning
confidence: 99%
“…Tool life enhancement [44] CuO nanoparticles with mineral oil Increase the service life of the cutting tool up to 604% [45] Al2O3 with soybean oil Increase almost 177% of the tool life than base fluid [46] Al2O3/MWCNT hybrid nano fluid with vegetable oil Improved the tool life much more better than base fluid and single nanofluid (Al2O3) [47] TiO2 with deionized water 70% more tool life than water [30] Al2O3 with carbon nanotube (CNT) in vegetable oil 23% enhancement [48] Al2O3 with vegetable oil 23.5% enhancement in tool life [49] Graphene with vegetable oil 178-190% of tool life enhancement [50] Ethylene glycol based TiO2 Tool life is 54.9 minutes.…”
Section: Authors Cutting Fluidmentioning
confidence: 99%
“…The authors confirmed that surface roughness, cutting temperature and residual stress were reduced compared with flood cutting. Minh et al [35] noticed during milling of 60Si 2 Mn steel with Al 2 O 3 nano fluids under MQL condition that 0.5% volume of Al 2 O 3 nano particles reduced the cutting force, surface roughness and tool wear compared to normal cooling system. Gupta et al [36] executed several replacements under dry machining, nitrogen cooling, nitrogen with minimum quantity lubrication and ranque-Hilsch vortex tube in turning AL 7075-T6 alloy.…”
Section: Introductionmentioning
confidence: 99%